Contact Stress Analysis of Traction Drives of a New Type Bearing Reducer - Shu Hongyu; Zhao Liang; Yu Yijie (Jixie chuandong)
An arc is constructed at the end of the planetary wheel profile shaft of the planetary traction drive, and the contact point between the arc and the outer ring and the end face of the solar wheel shaft is kept on the radial traction contact line. A new type of a more compact bearing reducer is designed by replacing thrust bearings cleverly. In this study, the radial contact stress and flange stress of the contact line are analyzed based on the assembly interference, the full arc element line modification and the influence of the contact line edge chamfering. Several sets of 3D ideal models are established and analyzed by Abaqus software. The results show that the edge stress concentration exists in the contact lines of the outer ring, planetary wheel and solar wheel of the bearing reducer. Reasonable contact-element trimming and edge chamfering can make contact stress uniform and improve edge effect. The best way to improve the contact stress of traction drives is to modify the contact element and chamfering the edge simultaneously. The distribution and size of the contact stress at the flange are basically the same under different convexity modification, and the axial and radial contacts between the contact line of the planet wheel and the outer ring and the contact line of the sun wheel and the flange can remain on a traction line.